The Effect of Psychometric Analysis Series Training on the Item Analysis Ability of High School Teachers in Bandung. Issue 4 (March 2020) - Jatnika, R; Purwono, U; Djunaidi, A; Haffas, M
Abstract: The Psychometric Analysis Series (PAS) is software developed for item analysis, which consists of item difficulty, item discrimination, distractor power, reliability and descriptive statistics of a test. This study was conducted to look at the effect of the Psychometric Analysis Series training on the Item Analysis Ability of high school teachers in Bandung. The study was conducted using a one-group pretest-posttest design. The ability of Item Analysis is measured using an instrument that is scored between 0 to 10. The training participants consisted of 35 high school teachers in Bandung. The data obtained were analyzed using the t-test. The results showed a significant increase in the ability of item analysis in the posttest compared to pretest (t = 8, 777; p = 0, 000). Based on these results it can be concluded that the Psychometric Analysis Series training can improve the ability of item analysis of high school teachers in Bandung.